Polski przekład powieści Momo Kapora Zapiski pewnej Anny wobec oryginału - Filipek, Małgorzata (Przekłady Literatur Słowiańskich, 2025)
This paper analyses the translation of Momo Kapor’s novel Notes from an Ane (Zapiski pewnej Anny). The novel translated by Hanna Kirchner was published in Polish in 1979. The Polish edition is a selection of texts from two novels – Белешке једне Ане (Notes from an Ane) and Хеј, нисам ти то причала (Hey, I Didn’t Tell You That). The language of the main character’s monologues deserves special attention. Nevertheless, the teenage character’s adventures, the relationships between young people and adults, interactions with parents and the environment, as well as the search for love, friendship and a place in life remain universal themes that continue to hold appeal for contemporary readers.